The role of training, performance appraisal, and team collaboration in motivating innovation in Vietnam’s consumer finance sector - Le, Dinh Nghi; Nguyen, Thi Ngoc Huyen (Journal of Finance - Marketing Research, 2025)
In Vietnam’s fast-moving consumer finance industry, supporting employees in bringing ideas to life is key to organizational success. Grounded in Self-Determination Theory (SDT), this study investigates how Training and Development, Performance Appraisal, and Intrateam Collaboration Climate influence intrinsic and extrinsic motivation, thereby enhancing Innovative Job Performance. Data were collected from 254 employees in consumer financial institutions in Ho Chi Minh City and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM - SmartPLS 3.0). The findings reveal that all three HRM practices are significantly associated with both intrinsic and extrinsic motivation. Notably, extrinsic motivation demonstrates a stronger direct association with innovative job performance (β = 0.577) than intrinsic motivation (β = 0.270). Mediation analysis further confirms that intrinsic and extrinsic motivation partially mediate the relationships between HRM practices and innovative job performance. Our model was able to explain about 62% (R² = 0.619) of employees’ innovative job performance in Vietnam’s consumer finance sector, showing that the HRM practices studied play a strong role in shaping innovative behaviors at work. When employees are provided with meaningful training, evaluated with fairness, and supported by a collaborative team environment, they feel empowered to generate and implement new ideas. This study addresses a gap in understanding how integrated HRM strategies can foster innovation by motivating employees. The current investigation provides practical insights for managers and policymakers to design HRM practices that nurture a culture of innovation, ultimately enhancing organizational adaptability and competitiveness in the consumer finance sector.